Chemical components of marine sponge derived fungus fusarium proliferatum collected from Pulau Tinggi Malaysia (Komponen kimia kulat fusarium proliferatum diperolehi daripada Span Marin di Perairan Pulau Tinggi, Malaysia) - Mosadeghza .Z,; Zuriati Zakaria,; Asmat .A,; Gires .U,; Wickneswari .R,; Pittayakhajonwut .P,; Farahani .G.H.N, (Universiti Kebangsaan Malaysia, 2012)
Marine fungus Fusarium proliferatum derived from marine sponge collected along Pulau Tinggi, Malaysia was cultivated on Potato Dextrose Broth and incubated for 7 days at 30oC. The liquid cultures were then extracted using ethyl acetate. The crude extract was investigated for its anti-microbial activity and was passed through Sephadex column and the fractions were collected. Reverse phase HPLC was used to monitor the component of crude extract. HPLC guided purification of crude extract resulted in the isolation of linoleic acid, 4-hydroxy phenethyl alcohol, 2,5-furandimethanol and adenosine. Their structures were elucidated by spectroscopic methods.